Programa de lectura leer interculturalmente en estudiantes del primer nivel de la especialidad de lengua y literatura de la Universidad Nacional de la Amazonía Peruana 2023 - Gallardo Llumpo, Roberto Carlos (2025)
The present Reading Program Read Interculturally in Students of the First Level of the Specialty of Language and Literature of the National University of the Peruvian Amazon 2023, aimed to evaluate its effectiveness in cognitive, affective and behavioral intercultural competence in students of the first level of the Language and Literature specialty of the UNAP, for this the experimental design was used. The type of research applied was pre-experimental, where a before and after is compared in the students, which allows determining whether the student has improved their intercultural competencies with the knowledge that has been generated, or, on the contrary, the student does not show an improvement with respect to their intercultural competencies. We have a population of 50 students specializing in Language and Literature at the first level of the National University of the Peruvian Amazon 2023, which includes lagging students. To develop this program, there was a sample of 32 students from the first level of the Language and Literature specialty who made up the pre-experimental group. Finally, the application of the Read Interculturally Program, which was carried out through texts and questionnaires, allowed the collection of pertinent data, also through the SPSS 25 statistical program, resulted in a positive effect on intercultural competencies in the students of the first level of the specialty of Language and Literature of the National University of the Peruvian Amazon 2023.